Improving nitrous oxide (N₂O) emissions accounting in Kenya: Insights and measurement results relating to fertilizer practices, environmental drivers, and N isotopic composition - Ouma, T.; Agredazywczuk, P.; Barthel, M.; Otinga, A.; Njoroge, R.; Leitner, Sonja; Yuhao Zhu; Oduor, Collins; Oluoch, K. C.; Obozinski, G.; Six, Johan; Harris, E. (International Livestock Research Institute, 2025)
The use of mineral fertilizers in Sub-Saharan Africa (SSA) is crucial for enhancing agricultural productivity but also raises concerns about emissions of nitrous oxide (N₂O), a potent greenhouse gas. Despite their importance for agriculture, N₂O emissions remain poorly understood in SSA, limiting the development of accurate emissions inventories and the adoption of climate-smart agricultural practices.